IDENTIFIKASI MOLEKULER BROAD BEAN WILT VIRUS 2 (BBWV2) DAN CYMBIDIUM MOSAIC VIRUS (CYMMV) ASAL TANAMAN NILAM (POGOSTEMON CABLIN BENTH.) - Miftakhurohmah .; Gede Suastika; Tri Asmira Damayanti; Rita Noveriza (Universitas Lampung, 2015)
Molecular identification Broad Bean Wilt Virus 2 (BBWV2) and Cymbidium Mosaic Virus (CymMV) from patchouli plant (Pogostemon cablin Benth.). Several viruses have been reported to be associated with mosaic disease on patchouli plant in Indonesia. This study aims to identify the two viruses in patchouli cultivation in West Java by studying the molecular characterization. Mosaic symptomatic leaf samples taken from patchouli cultivation in Manoko (Bandung Barat District, West Java Province). RNA extraction was performed using Xprep Plant RNA mini kit. RNA amplification with RT-PCR technique using primers for the cp gene region of BBWV2 and CymMV. The PCR product was sent to PT. Science Genetics Indonesia to do sequencing, then analyzed nucleotide sequences. Results of RT-PCR were performed successfully obtained DNA bands with size accordance with the predictions of the primer design for BBWV2 and CymMV cp region. Further, based on nucleotide and amino acid sequence analyses, the two virus isolates were confirmed as BBWV2 and CymMV respectively. Phylogenetic analyses revealed that BBWV2 Manoko clustered with BBWV2 from Singapore (original host of Brazilian red-cloak), China (pepper) and South Korea (chili). Whereas, CymMV Manoko become one cluster with CymMV from India (Phaius sp.), Indonesia (Dendrobium), China (vanilla), Thailand (Oncidium), Hawai (Dendrobium) and South Korea Cymbidium).